Pengurangan simptom post-traumatic stress disorder (PTSD) terhadap restrukturisasi kognitif media Surat Al-fatihah pada korban KDRT - Dwi, Siska (Jurnal Riset Psikologi, 2023)
Domestic violence is a form of violence with a specific purpose so that it harms women, both physically, psychologically, economically, it is tried unilaterally and is not expected by the victim, causing negative reactions such as fear, helplessness, short future, difficulty sleeping, avoiding social zones. Acts of violence against wives by husbands lead to traumatic experiences. This condition causes PTSD in the victim. One of the triggers affecting PTSD is dysfunctional images. The emergence of dysfunctional images is due to cognitive distortions. Cognitive distortions form maladaptive beliefs that are directly responsible for producing dysfunctional emotions and unadaptive behavior. Cognitive restructuring of al-Fatihah media, namely one of cognitive healing by integrating theistic thinking and Islamic religious beliefs aims to change beliefs, dysfunctional images into beliefs, more functional images through the tadabbur of al-Fatihah verses. This study aims to look at the effect of giving al-Fatihah cognitive restructuring in reducing PTSD symptoms of victims of domestic violence. The study subjects were 2 people, the study design was one group pre-test post-test design. The measuring instrument in this study is the PTSD symptom scale containing 92 statements. The results of the research show that al-Fatihah's cognitive restructuring reduces PTSD symptoms in victims of domestic violence, reducing the score to 209 for the first subject, and 217 for the second subject. The results indicated that before giving cognitive restructuring of al-Fatihah media, the subject's PTSD symptoms were in the severe type, but after giving al-Fatihah's cognitive restructuring, the subject's PTSD symptoms were in the mild type. Thus, the conclusion of this study is that cognitive restructuring of al-Fatihah's message media reduces PTSD symptoms in victims of domestic violence